Shiga Toxigenic and Atypical Enteropathogenic Escherichia coli in the Feces and Carcasses of Slaughtered Pigs - Borges, Clarissa Araujo [UNESP]; Beraldo, Livia Gerbasi [UNESP]; Maluta, Renato Pariz; Cardozo, Marita Vedovelli [UNESP]; Cabilio Guth, Beatriz Ernestina; Rigobelo, Everlon Cid [UNESP]; Ávila, Fernando Antonio de [UNESP] (Mary Ann Liebert, Inc., 2012)
Escherichia coli is a pathogen of major importance in swine and public health. To determine the prevalence of Shiga toxigenic E. coli (STEC) and enteropathogenic E. coli (EPEC), samples were collected from the feces and carcasses of swines. In total, 441 samples were collected in four samplings, of which 141 samples tested positive for either the stx1, stx2, and/or eae genes. From the positive samples, one STEC and 15 atypical EPEC (aEPEC) isolates were obtained, and all originated from the same sampling. In addition to eae, lpfA(O157/OI-141), ehxA, toxB, and lpfA(O113) were present in the aEPEC isolates. The only stx2-containing isolate carried stx2e and belonged to serotype O103:HNT. Resistance to four or more antimicrobials was found in almost half of the isolates, and some isolates shared the same fingerprint patterns by enterobacterial repetitive intergenic consensus-polymerase chain reaction (ERIC-PCR). The presence of certain virulence genes and the high level of resistance to antimicrobials, as well as the possible fecal contamination of carcasses showed that some of the isolates are of public health concern.